PEMBERDAYAAN MASYARAKAT DALAM TANGGAP DARURAT BENCANA BANJIR MELALUI SUPPORT EDUKASI EVAKUASIDAN TRANSPORTASI PADA SARASEHAN JUMAT KLIWONAN - martono; Siti Khadijah; Dwi Ariani Sulistyowati (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: Flooding is common in Indonesia, particularly during the rainy season, due to the country’s many rivers. About 30% of these rivers flow through densely populated areas, increasing the risk of hydrometeorological disasters, including flash floods. Floods can cause significant damage, both material and non-material, and even loss of life. Purpose: This activity aims to enhance the awareness, preparedness, and skills of residents in flood evacuation and transportation during emergencies. Method: The community service program focused on empowering members of the "Saresehan Jumat Kliwonan" group in Gagakan Village, Klaten Regency, through education on flood evacuation and transportation. 26 participants attended, including villagers and group administrators. The program involved planning, execution, evaluation, and reporting. Results: The program was well-received, with significant improvements in knowledge and attitudes towards evacuation and transportation (p = 0.026). The next step is to incorporate this training into future community discussions. Conclusion: Training in evacuation and transportation can improve flood disaster preparedness. Optimizing the role of the "Saresehan Jumat Kliwonan" group is key to ensuring effective health services and socialization in the community.